1988
DOI: 10.2118/15642-pa
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Abrupt Reservoir Compaction and Surface Subsidence Caused By Pore Collapse in Carbonates

Abstract: A new procedure has been devekJped to predict the abrupt in-situ compaction and the associated surface subsidence above high-porosity carbonate fields that show pore collapse. The approach is based on an extensive laboratory compaction study in which the effects of carbonate type, porosity, core preparation, pore saturant, horizontal/vertical stress ratio, and loading rate on pore-collapse behavior were investigated.For a number of carbonate types, a trendline was established that describes the relationship be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 6 publications
0
23
0
Order By: Relevance
“…The interfossil porosity vs. depth curves for the Site 803 samples fall along a single trend, as predicted for a uniform sediment type by Smits et al (1988). The more scattered picture for the Site 807 samples probably reflects problems with the determination of the intrafossil porosity in material with variable microfossil abundance.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…The interfossil porosity vs. depth curves for the Site 803 samples fall along a single trend, as predicted for a uniform sediment type by Smits et al (1988). The more scattered picture for the Site 807 samples probably reflects problems with the determination of the intrafossil porosity in material with variable microfossil abundance.…”
Section: Discussionmentioning
confidence: 57%
“…They noted the presence of calcite overgrowth on discoasters and the dissolution of nannofossils in Site 586 samples from a depth of 150 mbsf, and the transition from soft ooze to stiff ooze and chalk at roughly 250 mbsf. Smits et al (1988) performed compaction experiments on moldic limestone as well as three different chalks. They established that subsequent to pore collapse, samples of similar lithology but different initial porosity tend to follow the same curve relating porosity to vertical effective stress.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For very porous or weakly consolidated reservoirs, the increase in effective stress may be sufficient to cause inelastic deformation of the reservoir rock (e.g., Jones and Leddra, 1989;Goldsmith, 1989). The consequences of such inelastic compaction can be economically severe and include surface subsidence and various production problems (e.g., Smits et al, 1988;Fredrich et al, 1998). Significant reduction of permeability may also accompany the compaction (Zhu and Wong, 1997b).…”
Section: Introductionmentioning
confidence: 99%
“…Dolomitic samples ranged from 33 to 47 MPa. Smits et al (11) reported a pore collapse vertical effective stress of 20 MPa to 50 MPa for mouldic limestone with porosity in the range of 27 to 39%. They also concluded that, for Danian and Maastrichtian chalk samples, there was a failure stress of 18 MPa to 60 MPa that were in a range of 35 to 50% porosity.…”
Section: Introductionmentioning
confidence: 99%